Cellular succinate metabolism and signaling in inflammation: implications for therapeutic intervention - Huang, Hong; Li, Gejing; He, Yini; Chen, Jing; Yan, Jianye; Zhang, Qin; Li, Liqing; Cai, Xiong (Frontiers in Immunology, 2024)
Succinate, traditionally viewed as a mere intermediate of the tricarboxylic acid (TCA) cycle, has emerged as a critical mediator in inflammation. Disruptions within the TCA cycle lead to an accumulation of succinate in the mitochondrial matrix. This excess succinate subsequently diffuses into the cytosol and is released into the extracellular space. Elevated cytosolic succinate levels stabilize hypoxia-inducible factor-1α by inhibiting prolyl hydroxylases, which enhances inflammatory responses. Notably, succinate also acts extracellularly as a signaling molecule by engaging succinate receptor 1 on immune cells, thus modulating their pro-inflammatory or anti-inflammatory activities. Alterations in succinate levels have been associated with various inflammatory disorders, including rheumatoid arthritis, inflammatory bowel disease, obesity, and atherosclerosis. These associations are primarily due to exaggerated immune cell responses. Given its central role in inflammation, targeting succinate pathways offers promising therapeutic avenues for these diseases. This paper provides an extensive review of succinate's involvement in inflammatory processes and highlights potential targets for future research and therapeutic possibilities development.